Human capital investment strategies in Europe - Friedhelm Pfeiffer; Karsten Reuß (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The paper analyses alternative investment policies and their consequences for the evolution of human capital in Europe based on a model of age dependent skill formation where the life span depends on investments during childhood. What makes the approach special is the analysis of the returns to education of alternative educational policies targeted at certain ages, countries, or productivity levels for two counterfactual policy regimes, one regime assuming the actual state of diversity and the other a unified Europe. Our results indicate that investments need to be directed more generally to people of younger ages in Europe. If equality is important enough additional investment should specifically be directed to disadvantaged individuals during childhood. Furthermore, high levels of life cycle income inequality and a high skill level increase the optimal amount of investments during younger adulthood. In a unified Europe, the effectiveness of policies to reduce inequality would be higher.
urn:nbn:de:bsz:180-madoc-31840
Keywords: D87; I12; I21; J13; 330; human capital investment; life cycle skill formation; welfare function; Europe